Termination of T cell priming relies on a phase of unresponsiveness promoting disengagement from APCs and T cell division - Bohineust, Armelle (J Exp Med, 2018)
T cells are primed in secondary lymphoid organs by establishing stable interactions with antigen-presenting cells (APCs). However, the cellular mechanisms underlying the termination of T cell priming and the initiation of clonal expansion remain largely unknown. Using intravital imaging, we observed that T cells typically divide without being associated to APCs. Supporting these findings, we demonstrate that recently activated T cells have an intrinsic defect in establishing stable contacts with APCs, a feature that was reflected by a blunted capacity to stop upon T cell receptor (TCR) engagement. T cell unresponsiveness was caused, in part, by a general block in extracellular calcium entry. Forcing TCR signals in activated T cells antagonized cell division, suggesting that T cell hyporesponsiveness acts as a safeguard mechanism against signals detrimental to mitosis. We propose that transient unresponsiveness represents an essential phase of T cell priming that promotes T cell disengagement from APCs and favors effective clonal expansion.